Engineering graphene oxide with ultrasmall SPIONs and smart drug release for cancer theranostics. Issue 13 (25th January 2019) - Luo, Yu; Tang, Yan; Liu, Tianzhi; Chen, Qian; Zhou, Xiaohan; Wang, Ning; Ma, Ming; Cheng, Yingsheng; Chen, Hangrong
Abstract : An intelligent nanoplatform is constructed by conjugating cis -aconitic anhydride-modified doxorubicin to weakly crystallized, ultrasmall SPION loaded graphene oxide (GO) nanosheets. More importantly, the composites present ultrasensitive breakage hydrolysis induced by pH alteration, achieving on-demand, gradual drug release in the tumor microenvironment. Abstract : A smart nanotheranostics nanoplatform was constructed using engineered graphene oxide and the in situ growth of ultrasmall superparamagnetic iron oxide particles (SPIONs). The construction of such a novel theranostics nanoplatform shows great potential in tumor theranostics, especially for T 1 -weighted magnetic resonance ( T 1 -MR) imaging guided, pH-sensitive chemotherapy.